Factors influencing intention to use smart home technology among elderly in Iraq: The case of Babylon and Diwanyah region - Al-Janabi, Ammar Hameed Shnain (2023)
Smart Home Services based on the Internet of Things (SHS-IoT) hold promising power to enhance the elderly's quality of life. Yet, elderly acceptance of SHS-IoT remains unexpectedly low and requires serious theoretical attention to investigate the factors influencing the elderly's intent towards SHS-IoT acceptance. These factors include expectations, needs, preferences, and ageing-related aspects. While the Senior Technology Acceptance Model (STAM) has been developed to investigate the interaction between elderly individuals and new technologies, there is a need for more comprehensive exploration to gauge the Intention to Use (ITU) of SHS-IoT among elderly. This exploration should include critical factors such as Psychological Barriers(PB), Safety/Security (SS), Perceived Behaviour Control (PBC), Perceived Cost (PC), and Personal Innovativeness(PI), which are currently absent from the existing STAM. Therefore, this study introduces a model aimed at empirically examining 15 factors to understand the elderly's ITU SHS-IoT impact. Surveys and experimental approaches gathered data via purposive sampling from 50 Iraqi elderlies aged 55 and above. The data was analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) to examine the relationship between the proposed factors. The findings of this study illustrated that SS has a strong and positive impact on the ITU SHS-IoT, while its moderating effect in the relation between the Attitude towards (AT) and ITU was found to be insignificant. The mediator effect of PBC was found to have a strong mediating relationship between PI and ITU. The PC significantly and adversely impacted ITU, whereas the PB positively affected the AT. Additionally, anxiety (ANX) and Self-Efficacy (SE) positively affect Perceived Ease of Use (PEOU), while Facilitating Conditions (FC), SE, and SS enhance the Perceived Usefulness (PU) of SHS-IoT. This study establishes a robust model elucidating the investigation of ITU SHS-IoT technology among the elderly. Its implications resonate in technological inclusion, autonomous living, intergenerational connectivity, and holistic well-being. Healthcare providers can strategically use these findings to educate and promote SHS-IoT acceptance, thereby fostering enhanced living standards for the elderly.